Emissions from fuel-operated heaters in battery-electric buses - Åsa M. Hallquist; Håkan Salberg (Atmospheric Environment: X)
Battery-electric buses have become more common in the urban environment. At low ambient temperatures the energy consumption due to heating of the passenger and driving compartment can be significant, and to preserve the range of the battery fuel-operated heaters can be used. The legislation regarding these heaters is less stringent compared to engine exhaust emission legislation e.g., Euro VI, and knowledge about these emissions is scarce. In this study, emissions from 34 fuel-operated heaters, running on hydrotreated vegetable oil (HVO), in battery-electric buses from an in-use bus fleet have been characterised both regarding gaseous (total hydrocarbon (THC) and nitrogen oxides (NOx)) and particle pollutants (particle number (PN), particle mass (PM), black carbon (BC) and size) during real-world dilution. The median PM and PN emissions varied between 0.96 and 8.4 mg (kg fuel)−1 and 4.4–127 × 1013 # (kg fuel)−1 for the heater types studied. Additionally, the significance of the heater emissions compared to engine exhaust emissions was analysed.